PREVALENCE OF PRE-ECLAMPSIA AND ECLAMPSIA AND MATERNO-FETAL OUTCOMES AT A HEALTH FACILTY IN DELTA STATE, NIGERIA: PREVALENCE AND OUTCOMES OF PRE-ECLAMPSIA AND ECLAMPSIA - Clement Aghoja, Ogheneovo; Ahwinahwi, Ufuoma Shalom; Ahwinahwi, Ufuoma Shalom; Arute, John Edjophe; Arute, John Edjophe; Oliseyenum, Delight Weluche (Ethiopian Journal of Reproductive Health, 2023)
BACKGROUND: Globally, pre-eclampsia and eclampsia complicate up to 4.6% and 1.4% of pregnancies respectively but disproportionally account for nearly 18% of all maternal death worldwide, with an estimated 62,000 to 77,000 deaths per year. OBJECTIVE: This study determined the prevalence of pre-eclampsia and eclampsia, and compared outcomes. METHODS: This was a retrospective cross-sectional study utilizing the case files of women admitted to the maternity ward of the obstetrics and gynaecology unit in Central Hospital, Ughelli from 1st August 2020 to 30th July 2022. Socio-demographic characteristics, maternal and fetal complications and outcomes, prevalence rate of preeclampsia and eclampsia, were presented as frequencies and percentages. RESULTS: Of the 6291 mothers which were delivered of their babies in the maternity ward of the obstetrics and gynaecology department, 120(1.9%) were diagnosed of pre-eclampsia and eclampsia; only 108 which had complete documentation were used for the study. Age range of the participants was 16-45years, the majority, 88(81.5%) were married, had secondary education, 70(64.8%) and higher; 42(38.9%) were nulliparous at admission and 67(62%) were unbooked at the antenatal clinic. Fifty –three (49.1%) had preeclampsia while 55(50.9%) had eclampsia. Majority, 107(99.1%) were discharged home alive and 75(69.4%) had no maternal complications. Number of fetuses delivered were 114, 95 (83.3%) were born alive, 68(59.6%) weighed less than 2500g, and 91( 95.8%) neonates had a good APGAR score at the 5th minute. CONCLUSION: The prevalence of pre-eclampsia and eclampsia was low, however there was high rates of perinatal deaths and occurrence of unfavourable materno-fetal complications.